The Influence Of Work Life Balance And Job Stress On Job Satisfaction Of Employees At PT. Rukun Mitra Sejati South Jakarta - Rayeskana Istighfarkhan Jaysan; Suci Ayu Sudari; Yuni Pambreni (Best Journal of Administration and Management, 2024)
This research aims to analyze the influence of work life balance and work stress levels on employee job satisfaction. The research method uses a quantitative approach involving PT Rukun Mitra Sejati respondents. Data was collected through a questionnaire that measured the variables work life balance, work stress, and job satisfaction. The results of the analysis show that there is a positive and significant influence between work life balance and employee satisfaction. This shows that the more balanced the balance between work life and personal life (work life balance), the higher the level of job satisfaction felt by employees. On the other hand, there is a negative and significant influence between the level of work stress and employee satisfaction. This means that the higher the level of work stress experienced by employees, the lower the level of job satisfaction they feel. This research also produces an R Square value of 0.580, which shows that the work life balance variable (X1) and the work stress variable (X2) together contribute 58% to the job satisfaction variable (Y). Thus, this research makes an important contribution in understanding the factors that influence employee job satisfaction, especially through aspects of work life balance and work stress levels. The practical implications of these findings can be used as a basis for companies to increase employee job satisfaction through improvements in work life balance management and employee work stress management.